PENUMBUHAN NANOPARTIKEL TITANIUM DIOKSIDA PADA SUBSTRAT FTO DENGAN METODE ELEKTRODEPOSISI - Saidatun Khofifah; Iwantono '; Awitdrus ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
TiO2 nanoparticles have been grown successfully by electrodeposition method on the surface of Fluorine Tin Oxide (FTO) substrate. The growth of TiO2 nanoparticles was done by using voltage of 2 Volt, 6 Volt, 10 Volt, 14 Volt and 18 Volt. This TiO2 was also demonstrated with two different temperature 37 oC and 50 oC. The samples were characterized by UV-Vis spectroscopy, X-ray Diffraction, Scanning Electron Microscope (SEM) and Energy Dispersion X-ray (EDX). The results of UV-Vis showed that TiO2 nanoparticles have the highest absorption at 18 Voltage. The result of XRD at 18 Volt showed that TiO2 has 5 peaks at 2θ: 25,497o, 38,176o, 38,176o, 51,887o, 54,911 o, and 62,093 o, with their crystal plane (1 1 1), (2 1 1 ), (2 2 2), (3 2 0), (4 0 0). The results of SEM showed that nanoparticles form is nearly spherical at a magnification of 35000 times. The results of EDX of the review indicate that Ti atoms have a percentage atomic of 17.66% and O of 70,39%.